Numerical modeling of technological stresses in manufacture of polymeric insulation of a wire - Zinnatullin, Renat Railevich; Trufanova, Natalia Mikhailovna (Computational Continuum Mechanics, 2009)
Numerical modeling of different cooling modes of a wire with polymeric insulation has been carried out. The process of cooling of the wire is accompanied by heat exchange between the polymer insulation, the environment and the conductor, formation of the polymer crystalline structure and considerable thermal emission induced by phase transition, and occurrence of technological stresses in the insulation. Temperature-conversional fields and technological stresses in the polymer have been obtained and studied. A criterion for forecasting cavern formation has been determined. The air-to-water cooling modes are offered, which makes it possible to avoid the occurrence of radial stretched stresses in insulation critical zones and to increase the insulation rate.